JUSTIFICATION OF THE USE OF THE HEART RATE VARIABILITY ASSESSMENT METHOD AS AN ELECTRONIC HEALTH TOOL IN PHYSICAL THERAPY BASED ON THE EXPERIENCE OF PREVIOUS RESEARCHERS - Сурін, Дмитрій; Заікіна, Ганна; Семеніхіна, Олена (SWorldJournal, 2024)
The article presents an analysis of the problem of using the heart rate variability assessment method as one of the digital-health tools, which allows monitoring the functional state of individuals during various types of loads, as well as determining the